2021
DOI: 10.1186/s12887-021-02810-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between study questionnaire-assessed need and school doctor-evaluated benefit of routine health checks: an observational study

Abstract: Background In Finland, school doctors examine all children at predetermined ages in addition to annual health checks by school nurses. This study explored the association of study questionnaire-assessed need for and school doctor-evaluated benefit of routine health checks conducted by doctors. Methods Between August 2017 and August 2018, we recruited a random sample of 1341 children in grades 1 and 5 (aged seven and eleven years, respectively) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Participation rates, reasons for non-participation and doctor-evaluated and parent-evaluated benefits or harm of appointments have been described previously. 13 In brief, with a participation rate of 75.5%, 1013 children participated in the study. This included 506 first graders (age 7–8 years) and 507 fifth graders (age 11–12 years) from 21 public elementary schools.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participation rates, reasons for non-participation and doctor-evaluated and parent-evaluated benefits or harm of appointments have been described previously. 13 In brief, with a participation rate of 75.5%, 1013 children participated in the study. This included 506 first graders (age 7–8 years) and 507 fifth graders (age 11–12 years) from 21 public elementary schools.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous research concluded that the concern-based need for a school doctor health check is an important predictor of doctor-evaluated benefit of the health check. 13 According to a systematic review on the effectiveness of school health services, a demand remains for assessment of routinely delivered school health services. 14 The WHO guideline on school health services recommends clarification of what is already being done and by whom, the identification of conditions to be targeted and the set of What is known about the subject?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…to questionnaires that assess the concerns of parents, teachers, and nurses regarding each child's physical, mental, and social health. 10 One quarter of children may need special interventions due to physical, mental, and social disorders. 11 In the preventive child healthcare of Netherlands, physicians and nurses identified psychosocial problems in one quarter of school-aged children and undertook actions such as advice or reassurance, consultation, referral to another professional, and/or follow-up for most of them.…”
Section: Open Accessmentioning
confidence: 99%
“…These criteria may be ethically more difficult to accept than criteria based on concerns regarding each child. Our previous research suggested that at least one in four children have no need for a health check by school doctor according to questionnaires that assess the concerns of parents, teachers, and nurses regarding each child’s physical, mental, and social health 10…”
Section: Introductionmentioning
confidence: 99%